Maternal hyperglycemia and postnatal high-fat diet impair metabolic regulation and autophagy response in the liver of adult female rats - Cruz, Larissa Lopes da [UNESP]; Sinzato, Yuri Karen [UNESP]; Paula, Verônyca Gonçalves [UNESP]; Fioretto, Matheus Naia [UNESP]; Gallego, Franciane Quintanilha [UNESP]; Barco, Vinícius Soares [UNESP]; Camargo, Ana Carolina Lima [UNESP]; Corrente, José Eduardo [UNESP]; Justulin, Luis Antonio [UNESP]; Rodrigues, Tiago; Volpato, Gustavo Tadeu; Damasceno, Débora Cristina [UNESP] (Cambridge University Press (CUP), 2025)
This study aimed to investigate the mechanisms by which the association between maternal hyperglycemia and postnatal high-fat diet (HFD) exposure compromises metabolic parameters and hepatic autophagy in adult female pups. For this, Sprague Dawley rats, female pups from nondiabetic (control = FC) or diabetic (FD) mothers, were fed a standard diet (SD) or HFD from weaning until adulthood (n minimum = 5 rats/group): FC/SD, FC/HFD, FD/SD, and FD/HFD. In adulthood, these rats were tested with the oral glucose tolerance test, euthanized, and serum biochemistry parameters were analyzed. Liver samples were collected to evaluate cytokines, redox status, and protein expression autophagy and apoptosis markers. Histomorphometric analyses and an assessment of lipofuscin accumulation were also performed to reflect incomplete autolysosomal digestion. The FC/HFD, FD/SD, and FD/HFD groups showed glucose intolerance and an increased number of hepatocytes. Furthermore, FD/SD and FD/HFD rats showed hyperlipidemia and insulin resistance. Adaptations in hepatic redox pathways were observed in the FD/SD group with increased antioxidant defense marker activity. The FD/SD group also exhibited increased autophagy protein expression, such as p-AMPK, LC3-II/LC3-I, and p62/SQSTM1, lipofuscin accumulation, and caspase-3 activation. After exposure to HFD, the adult female pups of diabetic rats had a reduced p-AMPK and LC3-II/LC3-I ratio, the presence of steatosis, oxidative stress, and inflammation. The reduction of autophagy, stimulated by HFD, may be of vital importance for the susceptibility to metabolic dysfunction-associated fatty liver disease induced by maternal diabetes.
Keywords: AMPK; Diabetes; DOHaD; Lipophagia; MAFLD